Platinum(II) Complexes with Tetradentate Schiff Bases as Ligands: Synthesis, Characterization and Detection of DNA Interaction by Differential Pulse Voltammetry - Lijun Li; Chao Tian; Cheng Wang; Guangyuan Wang; Lianzeng Wang; Jianlong Du (E-Journal of Chemistry)
Five sterically hindered platinum(II) complexes with tetradentate schiff bases as ligands, [Pt(L)] (L= N,N′-bisalicylidene-1,2-ethylenediamine (L1), N,N′-bisalicylidene-1,2-cyclohexanediamine (L2), N,N′-bis(5-hydroxyl-salicylidene)-1,2-cyclohexanediamine (L3), N,N′-bisalicylidene-1,2-diphenyl-ethylenediamine (L4) and N,N′-bis(3-tert-butyl-5-methyl-salicylidene)-1,2-diphenylethylenediamine (L5) ) have been synthesized and characterized by IR spectroscopy and elemental analysis. The sterical hindrance of antitumor drug candidates potentially makes them less susceptible to deactivation by sulphur containing proteins and helping to overcome resistance mechanisms. The interaction of these metal complexes with fish sperm single-stranded DNA (ssDNA) was studied electrochemically based on the oxidation signals of guanine and adenine. Differential pulse voltammetry was employed to monitor the DNA interaction in solution by using renewable pencil graphite electrode. The results indicate that ligands with different groups can strongly affect the interaction between [Pt(L)] complexes and ssDNA due to sterical hindrances and complex [Pt(L1)] has the best interaction with DNA among the five complexes.